NEUROLOGICAL COMPLICATIONS OF HEPATITIS C IN SERBIAN POPULATION: NEUROLOGICAL COMPLICATIONS OF HEPATITIS C - Peric, Stojan; Nikolic, Luka; Stojan; Stojan; Dajevic, Milica; Božović, Ivo; Ralic, Branislav; Basta, Ivana; Kacar, Aleksandra (Medical Research, 2024)
Introduction: Approximately 58 million people are living with chronic hepatitis C virus (HCV) infection across the globe. Over half of the patients develop at least one extrahepatic complication throughout the disease. Neuropsychiatric disorders have been described in up to 50% of HCV patients. Peripheral neuropathies seem to be the most common complication. Aim: To explore the wide range of neurological complications of chronic HCV infection in Serbian patients. Materials and Methods: From the medical electronic system of the Neurology Clinic, a sample of 79 HCV patients was obtained (57% were male, average age was 59.0 ± 13.7 years, and average hepatitis duration was 12.4 ± 7.8 years). Results: Of the 79 HCV patients registered, 14 (17.7%) were newly diagnosed at the Neurology Clinic. There were 29 different primary neurological diagnoses on record. The most frequent complication was polyneuropathy (PNP) seen in 28 (35.4%) patients. The most common type was distal symmetric PNP. The average age of patients with PNP was significantly higher compared to those without it. Prevalence of diabetes mellitus and heart disease was more common in patients with PNP. Furthermore, glomerulonephritis was registered only in HCV patients with PNP. Conclusion: Elderly HCV patients with comorbidities such as diabetes mellitus and/or heart disease seem to be at an increased risk of polyneuropathies and should be screened accordingly.